The distance between the religious values of parents and those of children in Israel - Luria, Ela (Frontiers in Psychology, 2024)
Prior research into the socialization of religious values between religious parents and their children suggests that in homogeneous religious family groups there are similarities between the religious values of the religious parents to that of their children. Research further shows that in religious-secular heterogeneous family groups, there is a significant distance between the religious parent and their teenagers in religious values. This study of Modern-Orthodox religiosity in Israel, however, suggests that religious distance in values is not dependent on family type (homogeneous/heterogeneous) rather it seems that when the transmitter of religious values is a religious parent in both religious homogeneous and religious-secular heterogeneous family groups there will be a distance in the socialization of religious values between the religious parent and their children; however, the study suggests that the effect sizes will be smaller in parent-child religious distance of values in Modern-Orthodox homogeneous family groups in comparison to the parent-child religious distance of values in Modern-Orthodox-secular heterogeneous family groups. Our study provides support for recent research suggesting that the transmission of religiosity from parents to their children might function as a mechanism of secularization.